Modeling Economic Growth and Energy Consumption in Arab Countries: Cointegration and Causality Analysis - Shahateet, Mohammed Issa (International Journal of Energy Economics and Policy, 2014)
This paper examines the relationship between energy consumption and real economic growth in 17 Arab countries: Algeria, Bahrain, Egypt, Iraq, Jordan, Kuwait, Lebanon, Libya, Morocco, Oman, Qatar, Saudi Arabia, Sudan, Syria, Tunisia, United Arab Emirates and Yemen. It uses an Auto Regressive Distributed Lag (ARDL) model to determine this econometric relationship using data during 1980-2011. After testing for unit root and cointegration, it identifies Granger causality between energy consumption and real economic growth. The analysis allowed for the verification of the four hypotheses that have been discussed widely in economic literature: Neutrality, Conservation, Growth, and Feedback hypotheses. Empirical findings support neutrality hypothesis in 16 out of 17 Arab countries. These findings, of no causality from economic growth to energy consumption and the other way round, imply that energy conservation will not have a significant impact on economic growth and economic growth will have insignificant effect on changes in energy consumption. They also suggest including other more important variables in the determination of economic growth, such as labor and capital. Keywords: economic growth; energy consumption; ARDL model; Granger causality; Arab countries. JEL Classifications: C33; O4; O13; Q43